Experiences and training needs of healthcare providers involved in the care of Ghanaian adolescents living with HIV: an interventional study - Anna Hayfron-Benjamin; Dorcas Obiri-Yeboah; Yemah Mariama Bockarie; Ernestina Asiedua; Ibrahim Baidoo; Angela D. Akorsu; Stephen Ayisi-Addo (BMC, 2020)
Abstract Background Caring for adolescents living with HIV/AIDS (ALHIV) can be overwhelming due to their unique needs. Ghana is currently among nine countries in West and Central Africa contributing to 90% of new paediatric infections in the sub-region with a growing population of ALHIV. Regardless, gaps in paediatric related care including healthcare providers (HCPs) capacity issues have been identified. This study sought to assess the competencies of adolescent-oriented healthcare providers before, and after interventionist training to inform recommendation that would guide the psychosocial care they give to ALHIV. Methods The study adopted a mixed methods approach with a non-randomized interventional study involving three-phase multi-methods. The sample consisted of 28 adolescent-oriented and multi-disciplinary healthcare providers at the Cape Coast Teaching Hospital (CCTH) in Ghana. Data were obtained in three phases, namely, a baseline survey, interventionist training, and post-training in-depth interviews. Quantitative data were analyzed using Stata version 13 for descriptive analysis while the qualitative data were analyzed thematically using NVivo version 11. Results Although the majority of the HCPs claim to be knowledgeable about adolescent health issues (n = 21, 75.0%), only about a third (n = 10, 35.7%) could correctly define who an adolescent is. The majority (n = 18, 64.3%) had not received any training on how to work with the adolescent client. The main areas identified for improvement in the ALHIV care in phase 1 included issues with psychosocial assessment, communication and treatment adherence strategies, creating an adolescent-friendly work environment, and availability of job aids/protocols. During the post-training interviews, participants reported an improved understanding of the characteristics of an adolescent-friendly site and basic principles for ALHIV care. They were also able to correctly describe the widely used adolescent health assessment tool; the HEEADSSS. Post intervention interviews also revealed HCPs perception on increased practice related confidence levels and readiness to implement new knowledge and skills gained. Conclusion This study has shown that targeted training on routine ALHIV care is effective in increasing HCPs knowledge, skills and confidence. Addressing the healthcare system/facility related gaps serves as an impetus for improved ALHIV care among HCPs.